Pengaruh Pelatihan Dan Pengembangan Sumber Daya Manusia Terhadap Produktivitas Karyawan Yang Berkelanjutan Pada PT Prabu Mitra Teknik - Ilahi, Raihan Ridho; Lestari, Tri (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to analyze the influence of training and human resource development programs on sustainable employee productivity at PT Prabu Mitra Teknik. The background of this research is the urgent need to strengthen workforce competencies in the MEP (Mechanical, Electrical, and Plumbing) construction industry, which is dynamic and demands high technical excellence and adaptability. A quantitative approach with an associative method was used in this study, supported by multiple linear regression analysis. The sample consisted of 55 employees selected using a saturated sampling technique. The results show that training has a positive and significant effect on employee productivity, while human resource development does not have a significant partial effect. However, both variables simultaneously have a significant influence on productivity, with a coefficient of determination of 55.6%. These findings highlight the importance of structured training strategies and the need for comprehensive evaluation of human resource development programs. This research also supports the Sustainable Development Goals (SDGs), particularly Goal 8, which promotes inclusive economic growth and decent work. The practical implication of this study is the recommendation to formulate more adaptive and strategic HR development policies to improve the organization's long-term competitiveness.